2016
DOI: 10.1111/boc.201600044
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscale imaging with cryo‐light and X‐rays: Larger than molecular machines, smaller than a cell

Abstract: In the context of cell biology, the term mesoscale describes length scales ranging from that of an individual cell, down to the size of the molecular machines. In this spatial regime, small building blocks self-organise to form large, functional structures. A comprehensive set of rules governing mesoscale self-organisation has not been established, making the prediction of many cell behaviours difficult, if not impossible. Our knowledge of mesoscale biology comes from experimental data, in particular, imaging.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 111 publications
(244 reference statements)
0
38
0
Order By: Relevance
“…The past 20 years, however, have seen a rapid expansion in the application, utilization, and integration of X-raybased microscopy into workflows aimed to assay three-dimensional biological structures. Use of soft X-rays has been proven capable of studying minimally-perturbed cells, with resolutions nearing that of electron microscopy, and it holds the exciting prospect of being able to thoroughly explore the cellular mesoscale architecture (123). The development and application of metallic stains for XRM, and the ability to direct such staining to specific targets, offers the promise of exploring the means by which the spatial organization of any protein of interest effects the spatiotemporal dynamic properties of cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The past 20 years, however, have seen a rapid expansion in the application, utilization, and integration of X-raybased microscopy into workflows aimed to assay three-dimensional biological structures. Use of soft X-rays has been proven capable of studying minimally-perturbed cells, with resolutions nearing that of electron microscopy, and it holds the exciting prospect of being able to thoroughly explore the cellular mesoscale architecture (123). The development and application of metallic stains for XRM, and the ability to direct such staining to specific targets, offers the promise of exploring the means by which the spatial organization of any protein of interest effects the spatiotemporal dynamic properties of cells.…”
Section: Discussionmentioning
confidence: 99%
“…The development and application of metallic stains for XRM, and the ability to direct such staining to specific targets, offers the promise of exploring the means by which the spatial organization of any protein of interest effects the spatiotemporal dynamic properties of cells. The physical properties of both SXT and XRM hold unique quantification opportunities, with linear absorption coefficients offering the ability to identify sub-cellular compartments (123) and stain densities in XRM presenting a unique means of measuring protein aggregation. Application of X-ray microscopy techniques in EM correlative studies have demonstrated the increased efficacy the approach offers and the resultant increases in sample throughput.…”
Section: Discussionmentioning
confidence: 99%
“…Viruses Vaccinia [20,21], Herpes Simplex Virus 1 [22,23], Hepatitis C [24] Primary cells Erythrocytes [25,26], lymphocytes [9,12,22,27], olfactory sensory neurones [28,29] Immortalised lines EFN-R [30], HEK293 [31,32], G361 [33], RK13 [34], Cos7 [35], MCF-7 [36,37], Huh7 [38], RBL-2H3 [39], RAW264.7 [40], T-cell CEM [41], HT1080 [5], HT29 [15], J774 [42], PtK2 [20,43,44], 3T3 [42,45], DF1 [20], PC12 [19], mouse adenocarcinoma [25,46] Virus-host interactions (membrane remodelling) [48] Mitochondrial fission [35] Chromatin reorganisation [22,23,28] Phenotypic switching in yeast [45] Assembly of viral factories [20] Cholesterol crystal formation in macrophages [40] Plasmodium haeme detoxification [17] and egress…”
Section: Bacteriamentioning
confidence: 99%
“…Addressing this resolution gap, and as a direct result of a growing appetite for ever more diverse, cutting-edge imaging applications, cryo-soft X-ray tomography (cryo-SXT) has developed into a key player in the field. Cryo-SXT is a 3D imaging method for the visualisation of cellular ultrastructure at an intermediate resolution [5] and specifically addresses the need for detailed, 3D information on cellular features in thick specimens, such as whole cells, with little or no chemical or mechanical modification (Figure 2). It allows the observation of biological events on a range of scales, with imaging of details as fine as the internal structure of larger viruses and bacteria to the ultrastructure of yeast, protozoa and mammalian cells (Table 1A) and their associated components such as the nucleus, endoplasmic reticulum, mitochondria, parts of the cytoskeleton and more [47].…”
Section: Introductionmentioning
confidence: 99%
“…
Using soft x-ray microscopy (SXM), we are able to image and quantitatively analyze the spatial organization of the organelles within cancer cells [1]. Crucial cellular activities, such as cancer invasion and metastasis, mostly take place within a three-dimensional extracellular matrix (ECM) [2].
…”
mentioning
confidence: 99%